High-thermal-conductivity anti-corrosion hydrophilic aluminum foil and preparation method thereof
By coating anti-corrosion coatings containing bishydroxypyridine quaternary ammonium salt and sulfonated graphene powder on the surface of the hydrophilic aluminum foil, the problem of insufficient anti-corrosion performance on the surface of conventional aluminum foil is solved, and the improvement of high thermal conductivity, corrosion and anti-bacterial properties is achieved.
Patent Information
- Application Number
- CN202510314729.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
AI Technical Summary
The anticorrosion performance of conventional hydrophilic aluminum foil surface coatings is poor and does not have anti-mold functions, which leads to a decrease in thermal conductivity and potential harm to the human body.
The bishydroxypyridine quaternary ammonium salt is introduced in the chain expansion stage of polyurethane emulsion and the addition of sulfonated graphene powder to the hydrophilic anti-corrosion coating. These components are used to improve the antibacterial and corrosion resistance of the aluminum foil surface.
It achieves the improvement of high thermal conductivity, corrosion and antibacterial properties of the aluminum foil surface, extends the service life and improves safety.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrophilic aluminum foil, in particular to a high-thermal-conductivity, corrosion-resistant hydrophilic aluminum foil and a preparation method thereof. Background Art
[0002] Hydrophilic aluminum foil is made of unprocessed aluminum foil after degreasing, washing, drying, and then coating with a hydrophilic coating. It is usually used in refrigeration equipment such as air conditioners and freezers. The presence of the hydrophilic coating on the surface can cause the moisture in the hot air to condense on the heat exchanger plate to form water droplets, and flow down along the sheet. This can avoid the formation of a "tower bridge" between the heat exchanger plates, which affects the ventilation effect of the heat exchanger, thereby improving the heat exchange efficiency of the refrigeration equipment.
[0003] However, the conventional hydrophilic aluminum foil surface coating has poor anti-corrosion performance and does not have anti-mold and other functions. Long-term use will not only reduce the thermal conductivity, but also cause harm to the human body. Therefore, it is very necessary to prepare a high thermal conductivity and anti-corrosion hydrophilic aluminum foil with antibacterial properties. Summary of the invention
[0004] The object of the present invention is to provide a high thermal conductivity, corrosion-resistant and hydrophilic aluminum foil and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high thermal conductivity, corrosion-resistant, hydrophilic aluminum foil and a preparation method thereof, comprising the following steps: Step 1: After dehydrating polyethylene glycol 2000, toluene diisocyanate is added, dibutyltin dilaurate is used as a catalyst, and the reaction is carried out at 75-85°C for 2-3 hours, and dimethylolpropionic acid and 1,4-butanediol are added to continue the reaction for 2-3 hours; the temperature is lowered and dihydroxypyridinium quaternary ammonium salt is added, and the temperature is raised to 60-70°C and the reaction is continued for 1-2 hours, acetone is added to adjust the viscosity of the system, triethylamine is added for neutralization reaction, and water is added for emulsification to obtain a polyurethane emulsion; Step 2 The polyurethane emulsion, the defoaming agent, the leveling agent, the wetting agent and the sulfonated graphene powder are mixed to obtain a hydrophilic anti-corrosion coating; Step 3: After pre-treating the aluminum foil, a hydrophilic anti-corrosion coating is coated on the surface of the aluminum foil, and the foil is dried to obtain a high thermal conductivity anti-corrosion hydrophilic aluminum foil.
[0006] Furthermore, in step 1, the amount of each component used, by weight, is 35 to 40 parts of polyethylene glycol 2000, 43 to 52 parts of toluene diisocyanate, 6 to 7 parts of dihydroxymethylpropionic acid, 6 to 9 parts of 1,4-butanediol, 4 to 6 parts of dihydroxypyridinium quaternary ammonium salt, 20 to 25 parts of acetone, and 5 to 8 parts of triethylamine.
[0007] Furthermore, in step 1, the solid content of the polyurethane emulsion is 30-40%.
[0008] Furthermore, the preparation method of the dihydroxypyridine quaternary ammonium salt comprises the following steps: S1: dissolving 3-hydroxypyridine in methanol, then adding a 33% by mass aqueous solution of dimethylamine and a 35% by mass aqueous solution of formaldehyde, reflux for 1-2 hours, distilling off the solvent under reduced pressure, and cooling to obtain 2-dimethylaminomethyl-3-hydroxypyridine; S2: 2-dimethylaminomethyl-3-hydroxypyridine and acetic anhydride are mixed, refluxed for 2-3 hours, evaporated under reduced pressure to remove impurities, and cooled to obtain 2-acetoxymethyl-3-acetoxypyridine; S3: Disperse 2-acetoxymethyl-3-acetoxypyridine in hydrobromic acid, stir and reflux for 1-2 hours, evaporate excess hydrobromic acid under normal pressure, cool and filter, and wash with cold acetone to obtain 2-bromomethyl-3-hydroxypyridine; S4: Disperse 2-bromomethyl-3-hydroxypyridine and diethanolamine in anhydrous ethanol, and reflux for reaction at 55-60°C for 12-15h; after cooling, add sodium hydroxide for reaction for 1-2h, remove ethanol by rotary evaporation, add ether to precipitate solid, and filter and remove ether by rotary evaporation to obtain dihydroxypyridine quaternary ammonium salt.
[0009] Furthermore, in the hydrophilic anti-corrosion coating, the content of each component, by weight, is 100 parts of polyurethane emulsion, 1 to 2 parts of defoaming agent, 1 to 2 parts of leveling agent, 1 to 2 parts of wetting agent, and 0.3 to 0.5 parts of sulfonated graphene powder.
[0010] Furthermore, in step 2, the method for preparing sulfonated graphene powder comprises the following steps: a. Disperse graphene oxide in deionized water and obtain a graphene oxide dispersion by ultrasonic dispersion; add 5-8wt.% sodium carbonate aqueous solution to adjust the pH of the graphene oxide dispersion to 9-10, and heat it in a water bath at 80-85°C; add 1.6g sodium borohydride and stir for 1-2h, let it stand and cool, and collect the precipitate to obtain reduced graphene oxide; b. Add sodium nitrite to deionized water to obtain a sodium nitrite solution, cool it down to 0-5°C in an ice-water bath, add p-aminobenzenesulfonic acid and HCl aqueous solution, keep the temperature for reaction for 30 minutes, and obtain an aromatic diazonium salt solution; add reduced graphene oxide, keep the temperature for stirring for 1-2 hours, then move to a water bath at 25-30°C for reaction for 1-2 hours, centrifuge, wash, dry, and grind to obtain sulfonated graphene powder.
[0011] Furthermore, in step 3, the aluminum foil is immersed in an ethanol solution, ultrasonicated for 10 to 15 minutes, then blown dry with nitrogen and immersed in a sodium bicarbonate solution for 30 to 60 minutes, rinsed with deionized water to remove the residual solution on the surface, and blown dry with nitrogen.
[0012] Furthermore, the concentration of the sodium bicarbonate solution is 0.5~1 mol / L.
[0013] Furthermore, in step 3, the hydrophilic anti-corrosion coating is coated on the surface of the aluminum foil to a coating thickness of 50 to 120 μm.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention coats a hydrophilic and anti-corrosion coating on the surface of the aluminum foil to obtain a high thermal conductivity and anti-corrosion hydrophilic aluminum foil. When preparing the hydrophilic and anti-corrosion coating, the present invention introduces a dihydroxypyridine quaternary ammonium salt in the chain extension stage of the synthetic polyurethane emulsion; the dihydroxypyridine quaternary ammonium salt uses 3-hydroxypyridine as a raw material, first reacts with dimethylamine and formaldehyde to obtain 2-dimethylaminomethyl-3-hydroxypyridine; then adds acetic anhydride to react to obtain 2-acetoxymethyl-3-acetoxypyridine; further, reacts with hydrobromic acid to obtain 2-bromomethyl-3-hydroxypyridine; finally, 2-bromomethyl-3-hydroxypyridine is reacted with diethanolamine. The dihydroxypyridine quaternary ammonium salt has good antibacterial properties and can effectively prevent bacteria and mold from growing on the surface of the aluminum foil.
[0015] In addition, the present invention further adds sulfonated graphene powder to the hydrophilic anti-corrosion coating, wherein the sulfonated graphene powder is obtained by reducing graphene oxide and then modifying it with an aromatic diazonium salt solution. Compared with conventional graphene powder, the sulfonated graphene has better dispersibility, avoids agglomeration in the coating, and the large sheet structure of graphene can effectively block the corrosive medium, thereby improving the corrosion resistance; in addition, the sulfonated graphene can also improve the hydrophilicity of the coating, reduce the contact angle between the aluminum foil surface and water, and improve the heat exchange efficiency. DETAILED DESCRIPTION
[0016] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0017] Materials and sources used in the embodiments of the present invention: defoaming agent comes from Guangdong Nanhui New Materials Co., Ltd., model Cl-368; leveling agent comes from Foshan Shunde Sansheng Trading Co., Ltd., model TEGO410; wetting agent comes from Zhuhai Jintuan Chemicals Co., Ltd., model KEPERDISP®-6463B; graphene oxide comes from Beijing Juguang Evonik Technology Co., Ltd., model C03043.
[0018] Embodiment 1: A high thermal conductivity, anti-corrosion, hydrophilic aluminum foil and a preparation method thereof, comprising the following steps: Step 1: S11: 200 mg of graphene oxide was dispersed in deionized water, and ultrasonic dispersion was performed to obtain a graphene oxide dispersion; 5 wt.% of sodium carbonate aqueous solution was added to adjust the pH of the graphene oxide dispersion to 9, and the dispersion was heated in a water bath at 80° C.; 1.6 g of sodium borohydride was added and stirred for 1 h, and the precipitate was collected after standing and cooling to obtain reduced graphene oxide; S12: 144 mg of sodium nitrite was added to 80 g of deionized water to obtain a sodium nitrite solution, which was cooled to 0°C in an ice-water bath, and 368 mg of p-aminobenzenesulfonic acid and 4 g of 1 / mol HCl aqueous solution were added, and the temperature was maintained for reaction for 30 min to obtain an aromatic diazonium salt solution; 200 mg of reduced graphene oxide was added, and the temperature was maintained for stirring for 1 h, and then the mixture was moved to a water bath at 25°C for reaction for 1 h, and then centrifuged, washed, dried, and crushed to obtain sulfonated graphene powder; Step 2: S21: 4.1 g of 3-hydroxypyridine was dissolved in methanol, and then 10 g of a 33% by mass dimethylamine aqueous solution and 12 g of a 35% by mass formaldehyde aqueous solution were added, and the mixture was refluxed for 1 h. The solvent was evaporated under reduced pressure, and the mixture was cooled to obtain 2-dimethylaminomethyl-3-hydroxypyridine; S22: 10 g of 2-dimethylaminomethyl-3-hydroxypyridine and 40 g of acetic anhydride were mixed, refluxed for 2 h, evaporated under reduced pressure to remove impurities, and cooled to obtain 2-acetoxymethyl-3-acetoxypyridine; S23: Disperse 10 g of 2-acetoxymethyl-3-acetoxypyridine in hydrobromic acid, stir and reflux for 1 h, evaporate the excess hydrobromic acid under normal pressure, cool, filter and wash with cold acetone to obtain 2-bromomethyl-3-hydroxypyridine; S24: Disperse 2-bromomethyl-3-hydroxypyridine and diethanolamine in anhydrous ethanol, and reflux at 55° C. for 12 h; after cooling, add sodium hydroxide for 1 h, remove ethanol by rotary evaporation, add ether to precipitate solid, and filter and remove ether by rotary evaporation to obtain dihydroxypyridine quaternary ammonium salt; Step 3: S31: After dehydrating 35g of polyethylene glycol 2000, 43g of toluene diisocyanate was added, dibutyltin dilaurate was used as a catalyst, and the reaction was carried out at 75°C for 2h, 6.7g of dihydroxymethylpropionic acid and 8.4g of 1,4-butanediol were added, and the reaction was continued for 2h; the temperature was lowered and 5g of dihydroxypyridinium quaternary ammonium salt was added, and the temperature was raised to 60°C and the reaction was continued for 1h, 20g of acetone was added to adjust the viscosity of the system, 6g of triethylamine was added for neutralization reaction, and water was added for emulsification to obtain a polyurethane emulsion with a solid content of 30%; S32: 100 g of polyurethane emulsion, 1 g of defoamer, 1 g of leveling agent, 1 g of wetting agent, and 0.3 g of sulfonated graphene powder are mixed to obtain a hydrophilic anti-corrosion coating; S33: The aluminum foil is immersed in an ethanol solution, ultrasonicated for 10 minutes, then dried with nitrogen and immersed in a 0.5 mol / L sodium bicarbonate solution for 30 minutes, rinsed with deionized water to remove the residual solution on the surface, and dried with nitrogen to obtain a pretreated aluminum foil; a hydrophilic anti-corrosion coating is coated on the surface of the aluminum foil with a coating thickness of 120 μm, and dried to obtain a high thermal conductivity anti-corrosion hydrophilic aluminum foil.
[0019] Embodiment 2: A high thermal conductivity, anti-corrosion, hydrophilic aluminum foil and a preparation method thereof, comprising the following steps: Step 1: S11: 200 mg of graphene oxide was dispersed in deionized water, and ultrasonic dispersion was performed to obtain a graphene oxide dispersion; 5 wt.% of sodium carbonate aqueous solution was added to adjust the pH of the graphene oxide dispersion to 9.5, and the dispersion was heated in a water bath at 85° C.; 1.6 g of sodium borohydride was added and stirred for 1.5 h, and the precipitate was collected after standing and cooling to obtain reduced graphene oxide; S12: 144 mg of sodium nitrite was added to 80 g of deionized water to obtain a sodium nitrite solution, which was cooled to 3°C in an ice-water bath, and 368 mg of p-aminobenzenesulfonic acid and 4 g of a 1 / mol HCl aqueous solution were added, and the temperature was maintained for reaction for 30 min to obtain an aromatic diazonium salt solution; 200 mg of reduced graphene oxide was added, and the temperature was maintained for stirring for 1.2 h, and then the mixture was moved to a water bath at 30°C for reaction for 1.5 h, and the sulfonated graphene powder was obtained by centrifugation, washing, drying, and crushing; Step 2: S21: 4.1 g of 3-hydroxypyridine was dissolved in methanol, and then 10 g of a 33% by mass dimethylamine aqueous solution and 12 g of a 35% by mass formaldehyde aqueous solution were added, and the mixture was refluxed for 1.5 h. The solvent was evaporated under reduced pressure, and the mixture was cooled to obtain 2-dimethylaminomethyl-3-hydroxypyridine; S22: 10 g of 2-dimethylaminomethyl-3-hydroxypyridine and 40 g of acetic anhydride were mixed, refluxed for 2.5 h, evaporated under reduced pressure to remove impurities, and cooled to obtain 2-acetoxymethyl-3-acetoxypyridine; S23: Disperse 10 g of 2-acetoxymethyl-3-acetoxypyridine in hydrobromic acid, stir and reflux for 1.5 h, evaporate the excess hydrobromic acid under normal pressure, cool, filter and wash with cold acetone to obtain 2-bromomethyl-3-hydroxypyridine; S24: Disperse 2-bromomethyl-3-hydroxypyridine and diethanolamine in anhydrous ethanol, and reflux at 55° C. for 14 h; after cooling, add sodium hydroxide for 1.5 h, remove ethanol by rotary evaporation, add ether to precipitate solid, and filter and remove ether by rotary evaporation to obtain dihydroxypyridine quaternary ammonium salt; Step 3: S31: After dehydrating 35g of polyethylene glycol 2000, 43g of toluene diisocyanate was added, dibutyltin dilaurate was used as a catalyst, and the reaction was carried out at 80°C for 2.5h, 6.7g of dihydroxymethylpropionic acid and 8.4g of 1,4-butanediol were added, and the reaction was continued for 2.5h; the temperature was lowered and 5g of dihydroxypyridinium quaternary ammonium salt was added, and the temperature was raised to 65°C and the reaction was continued for 1.5h, 20g of acetone was added to adjust the viscosity of the system, 6g of triethylamine was added for neutralization reaction, and water was added for emulsification to obtain a polyurethane emulsion with a solid content of 30%; S32: 100 g of polyurethane emulsion, 1 g of defoamer, 1 g of leveling agent, 1 g of wetting agent, and 0.4 g of sulfonated graphene powder are mixed to obtain a hydrophilic anti-corrosion coating; S33: The aluminum foil is immersed in an ethanol solution, ultrasonicated for 13 minutes, then dried with nitrogen and immersed in a 1 mol / L sodium bicarbonate solution for 45 minutes, rinsed with deionized water to remove the residual solution on the surface, and dried with nitrogen to obtain a pretreated aluminum foil; a hydrophilic anti-corrosion coating is coated on the surface of the aluminum foil with a coating thickness of 120 μm, and dried to obtain a high thermal conductivity anti-corrosion hydrophilic aluminum foil.
[0020] Embodiment 3: A high thermal conductivity, anti-corrosion, hydrophilic aluminum foil and a preparation method thereof, comprising the following steps: Step 1: S11: 200 mg of graphene oxide was dispersed in deionized water, and ultrasonic dispersion was performed to obtain a graphene oxide dispersion; 5 wt.% of sodium carbonate aqueous solution was added to adjust the pH of the graphene oxide dispersion to 10, and the dispersion was heated in a water bath at 85° C.; 1.6 g of sodium borohydride was added and stirred for 2 h, and the precipitate was collected after standing and cooling to obtain reduced graphene oxide; S12: 144 mg of sodium nitrite was added to 80 g of deionized water to obtain a sodium nitrite solution, which was cooled to 5°C in an ice-water bath, and 368 mg of p-aminobenzenesulfonic acid and 4 g of 1 / mol HCl aqueous solution were added, and the temperature was maintained for reaction for 30 min to obtain an aryl diazonium salt solution; 200 mg of reduced graphene oxide was added, and the temperature was maintained for stirring for 2 h, and then the mixture was moved to a water bath at 30°C for reaction for 2 h, and then centrifuged, washed, dried, and crushed to obtain sulfonated graphene powder; Step 2: S21: 4.1 g of 3-hydroxypyridine was dissolved in methanol, and then 10 g of a 33% by mass dimethylamine aqueous solution and 12 g of a 35% by mass formaldehyde aqueous solution were added, and the mixture was refluxed for 2 h. The solvent was evaporated under reduced pressure, and the mixture was cooled to obtain 2-dimethylaminomethyl-3-hydroxypyridine; S22: 10 g of 2-dimethylaminomethyl-3-hydroxypyridine and 40 g of acetic anhydride were mixed, refluxed for 3 h, evaporated under reduced pressure to remove impurities, and cooled to obtain 2-acetoxymethyl-3-acetoxypyridine; S23: Disperse 10 g of 2-acetoxymethyl-3-acetoxypyridine in hydrobromic acid, stir and reflux for 2 h, evaporate the excess hydrobromic acid under normal pressure, cool, filter and wash with cold acetone to obtain 2-bromomethyl-3-hydroxypyridine; S24: Disperse 2-bromomethyl-3-hydroxypyridine and diethanolamine in anhydrous ethanol, and reflux at 60° C. for 15 h; after cooling, add sodium hydroxide for 2 h, remove ethanol by rotary evaporation, add ether to precipitate solid, and filter and remove ether by rotary evaporation to obtain dihydroxypyridine quaternary ammonium salt; Step 3: S31: After dehydrating 35g of polyethylene glycol 2000, 43g of toluene diisocyanate was added, dibutyltin dilaurate was used as a catalyst, and the reaction was carried out at 85°C for 3h, 6.7g of dihydroxymethylpropionic acid and 8.4g of 1,4-butanediol were added, and the reaction was continued for 3h; the temperature was lowered and 5g of dihydroxypyridinium quaternary ammonium salt was added, and the temperature was raised to 70°C and the reaction was continued for 2h, 20g of acetone was added to adjust the viscosity of the system, 6g of triethylamine was added for neutralization reaction, and water was added for emulsification to obtain a polyurethane emulsion with a solid content of 30%; S32: 100 g of polyurethane emulsion, 1 g of defoamer, 1 g of leveling agent, 1 g of wetting agent, and 0.5 g of sulfonated graphene powder are mixed to obtain a hydrophilic anti-corrosion coating; S33: The aluminum foil is immersed in an ethanol solution, ultrasonicated for 15 minutes, then dried with nitrogen and immersed in a 1 mol / L sodium bicarbonate solution for 60 minutes, rinsed with deionized water to remove the residual solution on the surface, and dried with nitrogen to obtain a pretreated aluminum foil; a hydrophilic anti-corrosion coating is coated on the surface of the aluminum foil with a coating thickness of 120 μm, and dried to obtain a high thermal conductivity anti-corrosion hydrophilic aluminum foil.
[0021] Comparative Example 1: Conventional polyurethane coating was used instead of the hydrophilic anti-corrosion coating, and the other parameters were the same as those in Example 1.
[0022] S1: After dehydrating 35g of polyethylene glycol 2000, add 43g of toluene diisocyanate, use dibutyltin dilaurate as a catalyst, react at 75°C for 2h, add 6.7g of dihydroxymethylpropionic acid and 8.4g of 1,4-butanediol and continue to react for 2h; cool down and add 5g of dihydroxypyridinium quaternary ammonium salt, raise the temperature to 60°C and continue to react for 1h, add 20g of acetone to adjust the viscosity of the system, add 6g of triethylamine for neutralization reaction, and then add water for emulsification to obtain a polyurethane emulsion with a solid content of 30%; S2: 100 g of polyurethane emulsion, 1 g of defoamer, 1 g of leveling agent, and 1 g of wetting agent are mixed to obtain a hydrophilic anti-corrosion coating; S3: The aluminum foil is immersed in an ethanol solution, ultrasonicated for 10 minutes, then dried with nitrogen and immersed in a 0.5 mol / L sodium bicarbonate solution for 30 minutes, rinsed with deionized water to remove the residual solution on the surface, and dried with nitrogen to obtain a pretreated aluminum foil; a hydrophilic anti-corrosion coating is coated on the surface of the aluminum foil with a coating thickness of 120 μm, and dried to obtain a high thermal conductivity anti-corrosion hydrophilic aluminum foil.
[0023] Comparative Example 2: No sulfonated graphene powder was added, and the other parameters were the same as those in Example 2.
[0024] Step 1: S11: 4.1 g of 3-hydroxypyridine was dissolved in methanol, and then 10 g of a 33% by mass dimethylamine aqueous solution and 12 g of a 35% by mass formaldehyde aqueous solution were added, and the mixture was refluxed for 1.5 h. The solvent was evaporated under reduced pressure, and the mixture was cooled to obtain 2-dimethylaminomethyl-3-hydroxypyridine; S12: 10 g of 2-dimethylaminomethyl-3-hydroxypyridine and 40 g of acetic anhydride were mixed, refluxed for 2.5 h, evaporated under reduced pressure to remove impurities, and cooled to obtain 2-acetoxymethyl-3-acetoxypyridine; S13: Disperse 10 g of 2-acetoxymethyl-3-acetoxypyridine in hydrobromic acid, stir and reflux for 1.5 h, evaporate the excess hydrobromic acid under normal pressure, cool, filter and wash with cold acetone to obtain 2-bromomethyl-3-hydroxypyridine; S14: Disperse 2-bromomethyl-3-hydroxypyridine and diethanolamine in anhydrous ethanol, and reflux at 55° C. for 14 h; after cooling, add sodium hydroxide for 1.5 h, remove ethanol by rotary evaporation, add ether to precipitate solid, and filter and remove ether by rotary evaporation to obtain dihydroxypyridine quaternary ammonium salt; Step 2: S21: After dehydrating 35g of polyethylene glycol 2000, 43g of toluene diisocyanate was added, dibutyltin dilaurate was used as a catalyst, and the reaction was carried out at 80°C for 2.5h, 6.7g of dihydroxymethylpropionic acid and 8.4g of 1,4-butanediol were added, and the reaction was continued for 2.5h; the temperature was lowered and 5g of dihydroxypyridinium quaternary ammonium salt was added, and the temperature was raised to 65°C and the reaction was continued for 1.5h, 20g of acetone was added to adjust the viscosity of the system, 6g of triethylamine was added for neutralization reaction, and water was added for emulsification to obtain a polyurethane emulsion with a solid content of 30%; S22: 100 g of polyurethane emulsion, 1 g of defoamer, 1 g of leveling agent, and 1 g of wetting agent are mixed to obtain a hydrophilic anti-corrosion coating; S23: The aluminum foil is immersed in an ethanol solution, ultrasonicated for 13 minutes, then dried with nitrogen and immersed in a 1 mol / L sodium bicarbonate solution for 45 minutes, rinsed with deionized water to remove the residual solution on the surface, and dried with nitrogen to obtain a pretreated aluminum foil; a hydrophilic anti-corrosion coating is coated on the surface of the aluminum foil with a coating thickness of 120 μm, and dried to obtain a high thermal conductivity anti-corrosion hydrophilic aluminum foil.
[0025] Comparative Example 3: No dihydroxypyridinium quaternary ammonium salt was added, and the other parameters were the same as those in Example 3.
[0026] Step 1: S11: 200 mg of graphene oxide was dispersed in deionized water, and ultrasonic dispersion was performed to obtain a graphene oxide dispersion; 5 wt.% of sodium carbonate aqueous solution was added to adjust the pH of the graphene oxide dispersion to 10, and the dispersion was heated in a water bath at 85° C.; 1.6 g of sodium borohydride was added and stirred for 2 h, and the precipitate was collected after standing and cooling to obtain reduced graphene oxide; S12: 144 mg of sodium nitrite was added to 80 g of deionized water to obtain a sodium nitrite solution, which was cooled to 5°C in an ice-water bath, and 368 mg of p-aminobenzenesulfonic acid and 4 g of 1 / mol HCl aqueous solution were added, and the temperature was maintained for reaction for 30 min to obtain an aryl diazonium salt solution; 200 mg of reduced graphene oxide was added, and the temperature was maintained for stirring for 2 h, and then the mixture was moved to a water bath at 30°C for reaction for 2 h, and then centrifuged, washed, dried, and crushed to obtain sulfonated graphene powder; Step 2: S21: After dehydrating 35g of polyethylene glycol 2000, 43g of toluene diisocyanate was added, dibutyltin dilaurate was used as a catalyst, and the reaction was carried out at 85°C for 3h, 6.7g of dihydroxymethylpropionic acid and 8.4g of 1,4-butanediol were added, and the reaction was continued for 3h; the temperature was raised to 70°C and the reaction was continued for 2h, 20g of acetone was added to adjust the viscosity of the system, 6g of triethylamine was added for neutralization reaction, and water was added for emulsification to obtain a polyurethane emulsion with a solid content of 30%; S22: 100 g of polyurethane emulsion, 1 g of defoamer, 1 g of leveling agent, 1 g of wetting agent, and 0.5 g of sulfonated graphene powder are mixed to obtain a hydrophilic anti-corrosion coating; S23: The aluminum foil is immersed in an ethanol solution, ultrasonicated for 15 minutes, then dried with nitrogen and immersed in a 1 mol / L sodium bicarbonate solution for 60 minutes, rinsed with deionized water to remove the residual solution on the surface, and dried with nitrogen to obtain a pretreated aluminum foil; a hydrophilic anti-corrosion coating is coated on the surface of the aluminum foil with a coating thickness of 120 μm, and dried to obtain a high thermal conductivity anti-corrosion hydrophilic aluminum foil.
[0027] Experiment: The performance of the aluminum foils prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested.
[0028] Corrosion resistance: Soak the sample in 25°C, 5% sodium chloride saline for 120 hours. Take it out and observe whether there is bubbling, rust, etc. on the surface of the sample.
[0029] Hydrophilicity: The static contact angle is used to test the surface hydrophilicity.
[0030] Antibacterial properties: 5g beef extract, 5g sodium chloride, 10g peptone were mixed, and distilled water was added to 1L to obtain LB medium; 5g beef extract, 5g sodium chloride, 10g peptone, and 23g agar were mixed, and distilled water was added to 1L to obtain agar culture dishes. The pH values of the two culture dishes were adjusted to 7.2~7.4, and high temperature and high pressure treatment was performed. The frozen powder of the Escherichia coli strain was dissolved in the LB culture medium, and the Escherichia coli suspension was obtained by culturing in a shaker at 37°C for 24h; the Escherichia coli suspension was spread on the agar plate, and cultured in a constant temperature incubator at 37°C and 95% humidity for 24h; the bacterial colony was prepared with PBS to a concentration of 10 8 cfu / mL of bacterial suspension and then diluted to 10 5 cfu / mL; 50 μL of diluted bacterial solution was dripped onto the surface of aluminum foil, so that the bacterial solution was evenly spread to completely cover the surface of the sample, and then placed in a constant temperature incubator for 24 hours. Three parallel samples were set up for each group. The sample and the bacterial solution on it were transferred to a centrifuge tube, 5 mL of sterile PBS solution was added, and vortexed for 1 minute to obtain the eluate; 100 μL of the eluate was evenly spread on the agar medium plate, and the plate was taken out and photographed after being cultured in a constant temperature incubator for 24 hours. The number of colonies of each sample was counted, and the average number of colonies on the surface of each group of samples was calculated.
[0031] Antibacterial rate A = (N-N1) / N×100%; Where N is the number of colonies on the surface of the blank sample (uncoated aluminum foil); N1 is the number of colonies on the surface of the test sample.
[0032] The experimental results are shown in Table 1.
[0033] Table 1. Test results of various properties of aluminum foil
[0034] Conclusion: The data of Examples 1 to 3 show that the aluminum foil prepared by the present invention has good performance. The data of Example 1 and Comparative Example 1 show that, compared with conventional coatings, the hydrophilic anticorrosion coating prepared by the present invention improves the hydrophilicity and corrosion resistance of the aluminum foil surface, and at the same time imparts good antibacterial properties. The data of Example 2 and Comparative Example 2 show that the addition of sulfonated graphene powder is beneficial to improving the hydrophilicity of the aluminum foil surface and enhancing the corrosion resistance. The data of Example 3 and Comparative Example 3 show that the addition of dihydroxypyridinium quaternary ammonium salt can improve the antibacterial properties of the aluminum foil surface.
[0035] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high thermal conductivity, corrosion-resistant and hydrophilic aluminum foil, characterized in that: The following steps are involved: Step 1: After dehydrating polyethylene glycol 2000, toluene diisocyanate is added, dibutyltin dilaurate is used as a catalyst, and the reaction is carried out at 75-85°C for 2-3 hours, and dimethylolpropionic acid and 1,4-butanediol are added to continue the reaction for 2-3 hours; the temperature is lowered and dihydroxypyridinium quaternary ammonium salt is added, and the temperature is raised to 60-70°C and the reaction is continued for 1-2 hours, acetone is added to adjust the viscosity of the system, triethylamine is added for neutralization reaction, and water is added for emulsification to obtain a polyurethane emulsion; Step 2 The polyurethane emulsion, the defoaming agent, the leveling agent, the wetting agent and the sulfonated graphene powder are mixed to obtain a hydrophilic anti-corrosion coating; Step 3: After pre-treating the aluminum foil, a hydrophilic anti-corrosion coating is coated on the surface of the aluminum foil, and the foil is dried to obtain a high thermal conductivity anti-corrosion hydrophilic aluminum foil.
2. The method for preparing a high thermal conductivity, corrosion-resistant and hydrophilic aluminum foil according to claim 1, characterized in that: In step 1, the amount of each component used, by weight, is 35-40 parts of polyethylene glycol 2000, 43-52 parts of toluene diisocyanate, 6-7 parts of dihydroxymethylpropionic acid, 6-9 parts of 1,4-butanediol, 4-6 parts of dihydroxypyridinium quaternary ammonium salt, 20-25 parts of acetone, and 5-8 parts of triethylamine.
3. The method for preparing a high thermal conductivity, corrosion-resistant and hydrophilic aluminum foil according to claim 1, characterized in that: In step 1, the solid content of the polyurethane emulsion is 30-40%.
4. The method for preparing a high thermal conductivity, corrosion-resistant and hydrophilic aluminum foil according to claim 1, characterized in that: The preparation method of dihydroxypyridine quaternary ammonium salt comprises the following steps: S1: dissolving 3-hydroxypyridine in methanol, then adding a 33% by mass aqueous solution of dimethylamine and a 35% by mass aqueous solution of formaldehyde, reflux for 1-2 hours, distilling off the solvent under reduced pressure, and cooling to obtain 2-dimethylaminomethyl-3-hydroxypyridine; S2: 2-dimethylaminomethyl-3-hydroxypyridine and acetic anhydride are mixed, refluxed for 2-3 hours, evaporated under reduced pressure to remove impurities, and cooled to obtain 2-acetoxymethyl-3-acetoxypyridine; S3: Disperse 2-acetoxymethyl-3-acetoxypyridine in hydrobromic acid, stir and reflux for 1-2 hours, evaporate excess hydrobromic acid under normal pressure, cool and filter, and wash with cold acetone to obtain 2-bromomethyl-3-hydroxypyridine; S4: Disperse 2-bromomethyl-3-hydroxypyridine and diethanolamine in anhydrous ethanol, and reflux for reaction at 55-60°C for 12-15h; after cooling, add sodium hydroxide for reaction for 1-2h, remove ethanol by rotary evaporation, add ether to precipitate solid, and filter and remove ether by rotary evaporation to obtain dihydroxypyridine quaternary ammonium salt.
5. The method for preparing a high thermal conductivity, corrosion-resistant and hydrophilic aluminum foil according to claim 1, characterized in that: The content of each component in the hydrophilic anti-corrosion coating, by weight, is 100 parts of polyurethane emulsion, 1 to 2 parts of defoaming agent, 1 to 2 parts of leveling agent, 1 to 2 parts of wetting agent, and 0.3 to 0.5 parts of sulfonated graphene powder.
6. The method for preparing a high thermal conductivity, corrosion-resistant and hydrophilic aluminum foil according to claim 1, characterized in that: In step 2, the method for preparing sulfonated graphene powder comprises the following steps: a. dispersing graphene oxide in deionized water, and ultrasonically dispersing to obtain a graphene oxide dispersion; adding 5-8 wt.% sodium carbonate aqueous solution to adjust the pH of the graphene oxide dispersion to 9-10, and heating it in a water bath at 80-85°C; adding sodium borohydride and stirring for 1-2 hours, standing and cooling, and collecting the precipitate to obtain reduced graphene oxide; b. Add sodium nitrite to deionized water to obtain a sodium nitrite solution, cool it down to 0-5°C in an ice-water bath, add p-aminobenzenesulfonic acid and HCl aqueous solution, keep the temperature for reaction for 30 minutes, and obtain an aromatic diazonium salt solution; add reduced graphene oxide, keep the temperature for stirring for 1-2 hours, then move to a water bath at 25-30°C for reaction for 1-2 hours, centrifuge, wash, dry, and grind to obtain sulfonated graphene powder.
7. The method for preparing a high thermal conductivity, corrosion-resistant and hydrophilic aluminum foil according to claim 1, characterized in that: In step 3, the aluminum foil is immersed in an ethanol solution, ultrasonicated for 10 to 15 minutes, then dried with nitrogen and immersed in a sodium bicarbonate solution for 30 to 60 minutes, rinsed with deionized water to remove the residual solution on the surface, and dried with nitrogen.
8. The method for preparing a high thermal conductivity, corrosion-resistant and hydrophilic aluminum foil according to claim 7, characterized in that: The concentration of sodium bicarbonate solution is 0.5~1 mol / L.
9. The method for preparing a high thermal conductivity, corrosion-resistant and hydrophilic aluminum foil according to claim 1, characterized in that: In step 3, the hydrophilic anti-corrosion coating is coated on the surface of the aluminum foil to a coating thickness of 50 to 120 μm.
10. A high thermal conductivity, corrosion-resistant and hydrophilic aluminum foil prepared according to the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Additive-free sulfonated graphene / sulfur electrode slice and preparation method and application thereof
CN103682349A
Preparation method for magnetic graphene-based zinc oxide nanocomposite
CN107362803A
Preparation method of gemini quaternary ammonium salt polyurethane coating material with antibacterial performance
CN112646110A
Heat preservation type antibacterial polyester fiber and preparation process thereof
CN118531526A
Low-carbon steel hot-pressed thin plate and preparation process thereof
CN118932457A